My remarkable journey [large type] : a memoir - Johnson, Katherine G.; Hylick, Joylette; Moore, Katherine (Writer at National Geographic Kids); Page, Lisa Frazier (Harper Large Print, 2021)
The woman at the heart of the New York Times bestseller and Oscar-winning film "Hidden Figures" shares her personal journey from child prodigy in the Allegheny Mountains of West Virginia to NASA human computer and her integral role in the early years of the U.S. space program